EFFECT OF USING MODERN METHODS IN EXPLAINING THE TOPIC OF FUNCTIONS FROM MATHEMATICS TO STUDENTS - Usarov Komiljon (Western European Studies, 2024)
The topic of functions is a cornerstone in mathematics, pivotal for understanding advanced mathematical concepts and applications in various disciplines. Traditional teaching methods often fail to fully engage students or make the subject accessible. This study investigates the impact of modern teaching methods—such as technology-enhanced learning, visual aids, and interactive problem-solving—on student comprehension and engagement with the topic of functions. Using a quasi-experimental design, this research compares the performance and attitudes of two groups of secondary school students: one taught using traditional methods and the other with modern methods. Results indicate a significant improvement in comprehension and interest among students exposed to modern techniques, underscoring the importance of innovation in mathematics education
Keywords: Functions in mathematics; modern teaching methods; interactive whiteboard